Competency-based Assessment: Practical Considerations - Nedjari, Mounia; Bassou, Abderrahmane (جامعة الوادي - university of Eloued, 2021)
Abstract The ELT teachers’ perception of assessment in Algeria seems reflecting a bleak picture since the adoption of the competency-based approach to language teaching. This study hereby, seeks a diagnostic of the in-service EFL teachers’ current practices of alternative assessment to traditional testing. It is an exploration of its implementation in certain Secondary School ELT classrooms in the province of Tlemcen. The research was quantitatively designed and conducted through the use of a structured questionnaire and in which a group of EFL teachers was addressed with certain considerations such as age, educational qualification, and teaching experience. After a quantitative analysis of the data, they were discussed thoroughly and then interpreted. Results of the study results revealed an obvious misconception of EFL teachers in Algeria to the overall process of assessment, and their classroom practices to it seem to be controversial to the assessment theoretical conception. Nonetheless, through the study, it became non doubtful that the respondent participants let a little room work for alternative assessment which grants a broad spectrum of assessment opportunities to cater for the learners’ different learning styles. The research paper at hand would, hopefully, boost the EFL teachers’ assessment knowledge, emerge interest in it as a beneficial measurement tool, and change their attitudes towards it, for more efficiency, practicality and flexibility in the professional context.
Article
Keywords: English Language ; Competency-Based Assessment ; Traditional Testing ; Practicality ; Independent learning